Interactional Adaptation among Early-Married Couples: A Qualitative Study of Marital Communication and Role Negotiation - Puri Kusuma Dwi Putri; Mutia Rahmi Pratiwi Pratiwi; Ruth Mei Ulina Malau (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Early marriage is not a new phenomenon, it occurs not only in Indonesia but also globally. The Covid-19 pandemic has also contributed to the increasing number of early marriages in Indonesia. Women who enter early marriage experience complex problems, especially at the beginning of the marriage period as the adaptation phase they are going through. This research was conducted to describe women's experiences in going through the process of adapting to early marriage. This research uses a qualitative phenomenology method with the theory of Judee Burgon's interaction adaptation. The subjects of this research were five wives who married early at 16-19 years old. The findings indicate that the informants did not provide any conditions to their future husbands at the beginning of the marriage. Instead, the husbands' families established expectations that the wives should follow their husbands place of residence and be prepared to become housewives. The communication expectations from the informants were that the two-way communication process could take place well because, so far, husbands tended to be reluctant to discuss or argue, and communication was one-way. In dealing with conflict, informants stated that in the adaptation process